Harnessing Systems Thinking For Fundamental Change at an Institution of Higher Education in South Africa - Moloi, KC; Isabirye, AK (Journal of Ecohumanism, 2025)
In the face of increasingly complex challenges, contemporary institutions of higher education necessitate holistic and adaptive strategies for transformative change. This theoretical article explores the application of systems thinking as a foundational framework for enhancing effective organisational transformation within South African higher education institutions. Using literature review as the qualitative research genre, we systematically gathered information from reputable databases such as JSTOR, Scopus, PubMed, and Google Scholar to explore the principles of systems thinking and Senge’s Five Disciplines. The objective guiding our data search was to identify how systems thinking can address organizational dynamics and contribute to comprehensive change in practices, attitudes, and values. Our findings reveal that viewing organisations as dynamic, interconnected systems not only enhances leaders’ adaptability and decision-making processes but also promotes sustainable growth and organisational development. Through a thorough examination of systems thinking concepts, we underscore their efficacy in diagnosing organisational challenges, fostering collaborative interdepartmental relationships, and nurturing a culture of continuous learning. Based on our analysis, we recommend that South African universities embrace systems thinking as a critical approach to initiate and sustain fundamental change. The study ultimately advocates for a paradigm shift towards systems thinking, positioning it as essential for navigating the complexities of modern higher education environments and realizing institutional goals.